Metode Penyelesaian Hadist Mukhtalif: Kajian Ta'arudh al-Adillah - K Khairuddin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
Hadits position as law postulation to a certain extent providesperplexities to those arguing by. It happens due the existence ofbodily contradiction (ta’arudh) among the hadits themselves.Mujtahids (Muslim Scholars) have not reached any agreement onwhat solution could be applied to reconcile the contradiction.However, the Mujtahids’ method in solving the contradiction canbe track through four steps. There are: Al Jam’u wa al-Taufik(talfiq), Nasakh, Tarjih and Tauqif. Author argues that althoughthe scholars have not agreed with those four steps, they have to beapplied in a raw. Means that one cannot surpass others. This hasto be applied to gain well understanding about a hadistcomprehensively.